2010
DOI: 10.1021/jp907387q
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Forward Transfer of Organic LED Building Blocks Studied by Time-Resolved Shadowgraphy

Abstract: The patterned deposition of thin films is essential for many technological applications. One promising material deposition technique is laser-induced forward transfer (LIFT), where a thin layer coated on a transparent substrate is ablated by a laser pulse passing through the substrate. The ablated material is collected on a nearby receiver substrate in a pattern defined by the laser. The technique can be applied to heat and light sensitive materials, provided that they are not directly irradiated by the laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 57 publications
1
46
2
3
Order By: Relevance
“…Since the shock waves do not seem to influence the ejection regime or velocity, and detailed visualization requires a different experimental setup, we refer to Refs. [51,52] for a detailed discussion of shock waves.…”
Section: Jet and Spray Ejection By Partial Film Vaporizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the shock waves do not seem to influence the ejection regime or velocity, and detailed visualization requires a different experimental setup, we refer to Refs. [51,52] for a detailed discussion of shock waves.…”
Section: Jet and Spray Ejection By Partial Film Vaporizationmentioning
confidence: 99%
“…The ejection time scale is estimated to be only τ ∼ V=L ∼ 100 ns, assuming a velocity V ≈ 100 m=s and a length scale L ≈ 10 μm [18], resulting in challenging visualization conditions. So far, time-resolved visualization has been achieved for relatively thick liquid-film [19][20][21][22][23] and solid-phase [24][25][26] or pastetransfer [27,28] processes. Observations of LIFT processing of Au [29], Ni [30], Al [31], and Cr [32] do not provide sufficient spatial resolutions to track the process in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved imaging is a suitable method to visualize the ejection process and to gain further insight into the ejection process during LIFT. However, due to the challenging visualization conditions, time-resolved visualization has only been achieved for relatively thick liquid-film [21][22][23][24][25] and solid phase [26][27][28] or paste-transfer [29,30] processes. Attempts to visualize LIFT-processing of Au [31], Ni [32], Al [33], and Cr [34] do not provide sufficient spatial resolution to track the process in detail.…”
Section: Research Objectivesmentioning
confidence: 99%
“…In the following years several alternative LIFT based processes were developed. These alternative processes mainly focus on reducing the droplet size [61], but also on transferring more complex, often more sensitive materials like biological materials or complete devices like micro-electronics [26]. Over the years, the flexibility of the LIFT process led to a growing interest of the research community on this topic, as indicated by figure 2.1.…”
Section: Review On Lift Based Processesmentioning
confidence: 99%
See 1 more Smart Citation